2016
DOI: 10.1111/echo.13247
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Effect of Metabolic Syndrome without Hypertension on Left Ventricular Hypertrophy?

Abstract: Even in the absence of hypertension, MetS patients had significantly higher LV wall thickness, LV mass and LVMI, and incidence of LVH than control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…In this respect, our findings are also in agreement with those reported by Al-Daydamony and El-Tahlawi et al, who found a significant positive correlation between LVMI and TG levels in patients with metabolic syndrome without hypertension [27].…”
Section: Discussionsupporting
confidence: 93%
“…In this respect, our findings are also in agreement with those reported by Al-Daydamony and El-Tahlawi et al, who found a significant positive correlation between LVMI and TG levels in patients with metabolic syndrome without hypertension [27].…”
Section: Discussionsupporting
confidence: 93%
“…In this respect, our findings are also in agreement with those reported by Al-Daydamony and El-Tahlawi et al, who found a significant positive correlation between LVMI and TG levels in patients with metabolic syndrome without hypertension 26 .…”
Section: Discussionsupporting
confidence: 93%
“…Results from a study by Al-Daydamony MM et al [7] investigated the impact of metabolic syndrome (MetS) on LVM in a population with and without hypertension and their findings support our results. They found a significantly positive correlation between increased LVM and fasting blood glucose (r = 0.52, P < 0.0001), but also a significantly positive correlation between LVM and HbA1c (r = 0.42, P < 0.0001).…”
Section: Discussionsupporting
confidence: 88%
“…Increased LVM is associated with increased all-cause mortality [1, 2] and recurrent MI [4]. Hypertension [5] and aortic valve stenosis [6] are well-known causes of increased LVM, but dysglycemia has also been thought to influence LVM [7, 8]. The prevalence of dysglycemia is increasing worldwide and is a well-known risk factor of cardiovascular disease, which increases morbidity and mortality [9, 10].…”
Section: Introductionmentioning
confidence: 99%